The Effect of Quantum Learning Model on Attitude, Anxiety, and Achievement of Middle School Students Towards Mathematics - Mehmet Bahaddin Acat; Dilek Girit Yıldız (e-Kafkas Eğitim Araştırmaları Dergisi)
We conducted this research to investigate the impact of the Quantum Learning Model (QLM) on the academic achievement, attitudes toward mathematics, and anxiety levels of seventh-grade middle school students. A total of fifty-six 7th-grade students participated in the research. The research used a quasi-experimental model with a pretest-posttest control group. The experimental group used QLM during the research process, while the control group used the current learning approach. We conducted the research for 28 lesson hours. We collected data using attitude, anxiety scale, and academic achievement tests. We applied tests to both groups before and after the experimental procedure. We used independent-samples-T-tests and paired-samples-T tests in the analyses. We also evaluated the journals of students and the researcher. Accordingly, QLM had a positive effect on middle school students' academic achievement in mathematics. The posttest mean scores of attitudes decreased significantly in the control group. The experimental group experienced a decrease in post-test mean scores of anxiety, which was not statistically significant, whereas the control group experienced a statistically significant increase in post-test scores. Students and teachers have expressed positive opinions about the use of note-taking and mind maps, which enhance the durability of learning, the establishment of a classroom environment and atmosphere conducive to QLM, and the implementation of celebration activities.